KEY ELEMENTS OF HEURISTIC METHODS USAGE IN FOREIGN THEORY OF EDUCATION (ON THE BASIS OF GREAT BRITAIN) - Skvortsova Svetlana Valerevna (Sovremennye Issledovaniâ Socialʹnyh Problem, 2013)
Purpose: identify key elements of employing heuristic teaching methods in foreign theory of education. Methodology: a theoretical analysis of psychological and pedagogical literature on the issues of teaching creativity. Results: on the basis of theoretical analysis the main criteria of heuristic teaching methods are revealed: repeatability; absence of a single decision; need for group discussions; flexibility; wide variability; promotion of creative teaching; influence on the character of knowledge and relationships between the teacher and the students. Heuristic teaching methods have been divided into: methods of working with information, methods of working with problems, methods of research and methods of analyzing the decisions. The main characteristics of each group of methods are presented and certain recommendations for applying them in teaching creativity are given. Practical implications: the system of education.